2021
DOI: 10.1007/s11121-021-01259-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Interventions to Decrease Cyberbullying Perpetration and Victimization

Abstract: Evidence suggests that cyberbullying among school-age children is related to problem behaviors and other adverse school performance constructs. As a result, numerous school-based programs have been developed and implemented to decrease cyberbullying perpetration and victimization. Given the extensive literature and variation in program effectiveness, we conducted a comprehensive systematic review and meta-analysis of programs to decrease cyberbullying perpetration and victimization. Our review included publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 87 publications
1
46
0
4
Order By: Relevance
“…Recent studies have found similar estimates of cyberbullying during high school [58][59][60][61][62], and, that outside of the COVID-19 pandemic school year where cyberbullying decreased [63,64], cyberbullying perpetration increases through middle school and then stabilizes through high school [7,37,60,61,[65][66][67]. These findings taken together suggest this upward trend continues beyond middle school, and that middle school and early high school may be the best time to intervene [15,[38][39][40][41]68]. Results from Anthony et al [17] which, amongst other things, studied the relationship between verbal aggression and cyberbullying perpetration in high school seniors, suggest that the relationship between verbal aggression and cyberbullying perpetration might grow even stronger over time (i.e., the relationship between these two variables appears to be even stronger in high school than it is in middle school).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recent studies have found similar estimates of cyberbullying during high school [58][59][60][61][62], and, that outside of the COVID-19 pandemic school year where cyberbullying decreased [63,64], cyberbullying perpetration increases through middle school and then stabilizes through high school [7,37,60,61,[65][66][67]. These findings taken together suggest this upward trend continues beyond middle school, and that middle school and early high school may be the best time to intervene [15,[38][39][40][41]68]. Results from Anthony et al [17] which, amongst other things, studied the relationship between verbal aggression and cyberbullying perpetration in high school seniors, suggest that the relationship between verbal aggression and cyberbullying perpetration might grow even stronger over time (i.e., the relationship between these two variables appears to be even stronger in high school than it is in middle school).…”
Section: Discussionmentioning
confidence: 67%
“…Results from Anthony et al [17] which, amongst other things, studied the relationship between verbal aggression and cyberbullying perpetration in high school seniors, suggest that the relationship between verbal aggression and cyberbullying perpetration might grow even stronger over time (i.e., the relationship between these two variables appears to be even stronger in high school than it is in middle school). In fact, a recent meta-analysis of anti-cyberbullying interventions found that they were most effective in decreasing perpetration and aggression when they helped build concrete skills [68,69]. In tandem, these results highlight the importance of early prevention efforts when it comes to verbal aggression in general, and cyberbullying in particular, and provide additional evidence for argumentative skills deficiency theory [69,70].…”
Section: Discussionmentioning
confidence: 90%
“…En las dos últimas décadas ante la prevalencia y gravedad del cyberbullying se han desarrollado numerosos programas para prevenir e intervenir esta modalidad de violencia en-tre iguales, sin embargo, son pocos los programas que muestran su eficacia de forma científica y rigurosa (Gaffney et al, 2019;Polanin et al, 2021). En este sentido, dada la extensa literatura y la variabilidad de programas, recientemente se han publicado diversas revisiones y metaanálisis que evidencian la eficacia de los programas en la reducción del cyberbullying (Gaffney et al, 2019;Özgür, 2020;Polanin et al, 2021). En concreto, en un reciente metaanálisis Gaffney et al (2019) indican que los programas contra el cyberbullying pueden reducir la perpetración en aproximadamente un 10-15% y la victimización en aproximadamente un 14%.…”
Section: Programas De Prevención E Intervención En El Cyberbullyingunclassified
“…En concreto, se ha comprobado su eficacia en la reducción del cyberbullying (victimización y agresión), pero también en el aumento de las conductas de ayuda y una mejor percepción de ayuda por parte del profesor. Acorde a la literatura previa es primordial que las acciones de intervención y prevención demuestren su eficacia (Gaffney et al, 2019;Polanin et al, 2021). Sin embargo, aunque sea una práctica muy poco común, también es importante que los programas ya validados se actualicen en función de las nuevas necesidades en una problemática tan cambiante como el cyberbullying.…”
Section: Discusión Y Conclusionesunclassified
“…Both mental health problems and reduced student performance often arise as a consequence of negative social experiences in school, such as peer victimization, which can include malicious teasing, threats of harm, stalking, racial- or gender-based discrimination, and/or physical or sexual assault. Peer victimization has been linked to a variety of negative behavioral and emotional outcomes for adolescents, including higher levels of mental health problems, drug use, and delinquency, and lower levels of self-esteem, school attendance, and academic achievement (Barchia & Bussey, 2010 ; Moore et al, 2017 ; Nishina et al, 2005 ; Polanin et al, 2021 ; Rueger et al, 2011 ; Storch et al, 2005 ; Sullivan et al, 2006 ; Thijs & Verkuyten, 2008 ).…”
Section: Introductionmentioning
confidence: 99%